Pengaruh Empowerment dan Sistem Insentif Terhadap Kinerja Karyawan (Studi Pada PT Federal International Finance Group Samarinda) - Dhanardhono Satrio Wiwoho; Sukisno Selamet Riadi; Dirga Lestari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACT Dhanardhono Satrio Wiwoho, 2017. The Influence of Empowerment and Incentive System Toward Employee Performance (On Employees of PT Federal International Finance Group Samarinda). Under the guidance of Prof. Dr. Sukisno Selamet Riadi and Dr. Dirga Lestari AS, SE., M.Si.            This Study aimed to test whether empowerment and incentive system towards employee performance on employees of PT Federal International Finance Group Samarinda. Independent variabel in this study is the empowerment and incentive system. The dependent variabel is employee performance. This research was conducte on employees of PT Federal International Finance Group Samarinda Branch consisting of 65 respondents.This type research is quantitative research. Method data collection using the questionnaire. Data analysis using multiple linear regression. The results showed that empowerment and incentive system is positive and significant effect towards employee performance. Keywords: Empoerment, Incentive System and Employee Performance